2019
DOI: 10.1002/cncr.32405
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of uptake of contralateral prophylactic mastectomy in women with nonhereditary breast cancer

Abstract: Background The rates of contralateral prophylactic mastectomy (CPM) are increasing in women with breast cancer. Previous retrospective research has examined clinical and demographic predictors of the uptake of CPM. However, to the authors' knowledge, there has been very little prospective research to date that has examined psychosocial functioning prior to breast cancer surgery to determine whether psychosocial functioning predicts uptake of CPM. The current study was conducted to evaluate demographic, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
9
1
1
Order By: Relevance
“…[14][15][16][17][18] Consequently, earlier age at diagnosis and family history of BC/OC have been shown to be positively correlated with the decision to have CRRM in women with BC, regardless of genetic testing outcome. [19,37,38,46,[60][61][62] In this study, we did not observe any association between age at diagnosis and surgical decision when adjusted for GT result. However, all patients included in this study were 45 years old or younger, which hindered the ability to evaluate the impact of age at diagnosis on surgical decision making.…”
Section: Timely Cancer Genetic Counseling and Testing Young Women With Breast Cancercontrasting
confidence: 68%
See 1 more Smart Citation
“…[14][15][16][17][18] Consequently, earlier age at diagnosis and family history of BC/OC have been shown to be positively correlated with the decision to have CRRM in women with BC, regardless of genetic testing outcome. [19,37,38,46,[60][61][62] In this study, we did not observe any association between age at diagnosis and surgical decision when adjusted for GT result. However, all patients included in this study were 45 years old or younger, which hindered the ability to evaluate the impact of age at diagnosis on surgical decision making.…”
Section: Timely Cancer Genetic Counseling and Testing Young Women With Breast Cancercontrasting
confidence: 68%
“…Although higher CRRM rates with early-stage disease have previously been reported, disease stage was not shown to be associated with CRRM in our study. [19,37,61] Although cancer GT can provide valuable information in risk assessment and promote risk-appropriate management, some test results have the potential to lead to unnecessary interventions. Variants of uncertain significance (VUSs) in cancer predisposition genes do not have any clinical implications, and should not be used in risk assessment or risk management considerations.…”
Section: Timely Cancer Genetic Counseling and Testing Young Women With Breast Cancermentioning
confidence: 99%
“…A study [53] which used the Markov model to simulate survival outcomes in non-BRCA carriers after CPM and no CPM, found a less than 1% 20-year overall survival benefit after CPM. Other studies found between 45% and 48% improved 15 to 20-years survival rates in patients with BRCA1/2 mutations who got CPM compared to patients who got unilateral mastectomy or breast conserving surgery [51,59].…”
Section: Patient Rationales For Choosing Contralateral Prophylactic Mmentioning
confidence: 96%
“…Others situations, such as young patients, minor genetic mutations (CHEK2, TP53, ATM, PALB2, PTEN, CDH1), or family history without known gene mutation, have shown no evidence of any benefits of prophylaxis mastectomy [54]. Nevertheless, prophylaxis mastectomy is still being used with increasing preference in non-BRCA patients due to low breast satisfaction levels, fear of recurrence, and cosmetic symmetry [55,56]. A recent study reported that PIK3CA hotspot mutations were detected in 37/56 (66.1%) and 23/27 (85.2%) of DNA samples isolated from CellSearch ® cartridges in early and metastatic breast cancer, respectively [57].…”
Section: Discussionmentioning
confidence: 99%